2018
DOI: 10.1021/jacs.8b07525
|View full text |Cite
|
Sign up to set email alerts
|

Probing Dynamic Library of Metal-Oxo Building Blocks with γ-Cyclodextrin

Abstract: Formation of one of the most representative polyoxometalate (POM) archetypes, namely the Lindqvist anion MO with M = Mo or W, was considered as elusive in aqueous solution. Herein, we report on the host-guest stabilization of the MO species with M = Mo or W from aqueous solution using γ-cyclodextrin as trapping agent. The adduct {MO@γ-CD} reveals remarkable hydrolytic stability that offers new opportunities for exploring potentialities of molybdates or tungstates in the field of biology and medicine, when comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 29 publications
2
85
0
Order By: Relevance
“…131 Salts of the larger anion, [Mo VI 36 O 112 (OH 2 ) 16 ] 8À ( Fig. 10E and Table 4) can be crystallized from systems at pH lower than 2.8 141 and its identity in solution was confirmed by 95 Mo NMR 18,132 has been proposed. 6 Equilibrium constants obtained by different research groups based on potentiometric and NMR spectroscopic studies under the same conditions agree quite well (Table 4).…”
Section: Polyoxomolybdates (Pomos)mentioning
confidence: 90%
See 1 more Smart Citation
“…131 Salts of the larger anion, [Mo VI 36 O 112 (OH 2 ) 16 ] 8À ( Fig. 10E and Table 4) can be crystallized from systems at pH lower than 2.8 141 and its identity in solution was confirmed by 95 Mo NMR 18,132 has been proposed. 6 Equilibrium constants obtained by different research groups based on potentiometric and NMR spectroscopic studies under the same conditions agree quite well (Table 4).…”
Section: Polyoxomolybdates (Pomos)mentioning
confidence: 90%
“…The {Mo 6 } anion is the only colored IPOMo (yellow, l max = 325 nm, O b -Mo VI charge transfer) structurally based on six monounits MoO t (O t -terminal oxygen atom), rather than three cis MoO t2 units. {Mo 6 } does not exist in any notable concentration in pure aqueous solution and requires solvents with lower dielectric constants 147 or macrocycles 132 for stabilization due Fig. 11 Speciation of IPOMos in an aqueous solution with the concentration of Mo VI 0.1-0.4 M based on works.…”
Section: Hexamolybdate [Mo VImentioning
confidence: 99%
“…Their employment as complexing agents may, thus, result in shifting thermodynamic equilibriums and entrapping novel or elusive species because of maximizing entropy by reducing solvation energy. For instance, recently, we demonstrated that introduction of γ-CD modified the speciation in molybdate and tungstate solutions favors the Lindqvist-type poly-anion that has never been observed before in aqueous solution [15]. It, therefore, appears clear that α-CD assists the construction of the D6R unit (Si 12 O 30 12− ) and greatly contributes to its stabilization because formation of such a silicate anion is known to not occur spontaneously in aqueous alkaline silicate solutions.…”
Section: Introductionmentioning
confidence: 87%
“…The complexation of closo ‐B 12 X 12 2− to the hydrophobic inner cavity of CDs appears counterintuitive at first glance, due to the doubly negative charge of these clusters and their high water solubility (hydrophilicity). The high affinity of such large anionic clusters, not only borate clusters but also others such as polyoxometalates or octahedral metal clusters, to hydrophobic cavities as well as to neutral surfaces, membranes, and proteins has been described as the chaotropic effect that presents a topic of considerable current interest. Accordingly, the propensity of anionic clusters to associate to hydrophobic cavities has been attributed to ( i ) the comparative ease of desolvation of the large clusters in combination with ( ii ) the stabilization of the resulting assemblies by dispersion interactions, promoted by the high polarizability of these large anions.…”
Section: Figurementioning
confidence: 99%